Influence of Spousal Support on the Quality of Life of Women Living with Breast and Gynaecological Cancers in Ibadan, Nigeria - Chizoma M. Ndikom; Joel O. Aluko; Abimbola Adeoye (African Journal of Behavioural and Scale Development Research, 2019)
Breast and gynaecological cancers are the commonest cause of death among females (Inoue-Choi, Robien, &Lazovich, 2013). This research was conducted to establish the influence of spousal support on Quality of Life (QoL) of Women Living with Breast and Gynaecological Cancers (WLWBGCs) in a Nigerian tertiary hospital. The study used descriptive cross-sectional design to study 160 WLWBGC purposively selected from the Radiation Oncology unit and the Surgical Outpatients Clinic of the hospital. A structured questionnaire was used to collect relevant data from the participants after obtaining ethical clearance and consent form. The data were analysed using descriptive (mean, standard deviation, and frequency/percent), and inferential statistics (Chi- square) with the aid of Statistical Package for Social Sciences (SPSS) software. The level of significance was taken to be 0.05. The women's QoL was due to the fact that more than half of their population experience poor physical, emotional, social, sexual and spiritual life. Although some of the women received emotional, informational and instrumental support from their spouses, the spousal supports provided did not significantly improve their QoL (X2 = 2.880, p-v = 1.113). Therefore, since spousal supports did not influence the QoL of WLWBGCs, further studies focusing on improving the QoL of this category of women is therefore recommended.